HUBUNGAN ANTARA AKTIVITAS FISIK DAN DURASI TIDUR DENGAN OBESITAS PADA SISWA SMA N 3 SEMARANG - Dita Retno Anhhitasari; Cahyo Hunandar (JURNAL RISET GIZI, 2015)
Background: one of the nutritional problems in Indonesia is obesity. The prevalence of obesity among adolescents aged 13-15 years on the anthropometric index BMI / U is equal to 2.5% obesity (Riskesdas, 2013). Objective: to determine the relationship between physical activity and the duration of sleep with obesity in students of SMA N 3 Semarang Methods: his study included community nutrition research using a matchless case control design with 14 samples and controls of 14 samples. Data collected included anthropometric measurements, 2x24 hour physical activity with diary methods, sleep duration forms, personal data and general description of the school. The test used to determine the relationship between obesity and physical activity is the Fisher Exact Test, while the test used to determine the relationship between sleep duration and obesity is Chi Square Tests with α = 0.05 Results: Physical activity of SMA N 3 Semarang students compared to AMB which had mild activity in the case group was 100% while in the control group it was 50%, which had short sleep duration in 85.7% cases and 35.7% in controls. There is a significant relationship between physical activity and obesity (p = 0.006). There is a significant relationship between sleep duration and obesity (p = 0.007, OR = 10.8) and shows that samples that have short sleep duration are 10.8 times more at risk of obesity compared to samples that have sufficient sleep duration. Conclusion: there is a relationship between physical activity and sleep duration with obesity. It is recommended for the school to hold a weight assessment regularly every month and maximize physical activity activities during sports hours. For students to take a nap or be able to sleep before 10 o'clock at night.